2022
DOI: 10.3390/min12050561
|View full text |Cite
|
Sign up to set email alerts
|

Typomorphism of Native Gold (Geological-Industrial Types of Gold Deposits in the North-East of Russia)

Abstract: This study presents the typomorphic features of native gold grains from three different geological-industrial types (GIT) of gold deposits in the North-East of Russia: (1) gold–arsenic-sulfide in black shale strata (Natalka, Degdekan, Karalveem, Maldyak deposits), (2) gold–quartz veins in granitoids (Dorozhnoye, Butarnoye, Shkolnoye, Maltan deposits), and (3) gold–silver adularia in volcanogenic strata (Kupol, Olcha, Kubaka, Burgali, Primorskoe, Dalnee deposits). The reliability of the geological interpretatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…The identified high-grade shells on gold particles with deformation lines are extremely rare (Figure 2e,f). It is known that gold is an inert metal that practically does not change in exogenous conditions; however, we found that when staying in various exogenous conditions for billions of years and repeated redeposition, primary recrystallization and secondary recrystallization of gold occurred with the removal of silver and impurity elements [1,2,4,8]. When studying the internal structure of placer gold from the Quaternary deposits in the east of the Siberian Platform, it was found that almost all flake gold of type I with a size of 0.1-0.25 mm, of high fineness, is characterized by primarily recrystallized and secondarily recrystallized internal structure.…”
Section: Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…The identified high-grade shells on gold particles with deformation lines are extremely rare (Figure 2e,f). It is known that gold is an inert metal that practically does not change in exogenous conditions; however, we found that when staying in various exogenous conditions for billions of years and repeated redeposition, primary recrystallization and secondary recrystallization of gold occurred with the removal of silver and impurity elements [1,2,4,8]. When studying the internal structure of placer gold from the Quaternary deposits in the east of the Siberian Platform, it was found that almost all flake gold of type I with a size of 0.1-0.25 mm, of high fineness, is characterized by primarily recrystallized and secondarily recrystallized internal structure.…”
Section: Resultsmentioning
confidence: 74%
“…Thus, the identification of numerous deformation lines in placer gold indicates that these structures were formed in metamorphic strata and are an indicator for predicting ore deposits of gold-ferrous-quartzite mineralization. We draw attention to the fact that, although metamorphogenic gold has been studied earlier [1,3,4,8], this problem needs to be addressed in additional research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations